2022
DOI: 10.1093/biostatistics/kxac026
|View full text |Cite
|
Sign up to set email alerts
|

Designing three-level cluster randomized trials to assess treatment effect heterogeneity

Abstract: Summary Cluster randomized trials often exhibit a three-level structure with participants nested in subclusters such as health care providers, and subclusters nested in clusters such as clinics. While the average treatment effect has been the primary focus in planning three-level randomized trials, interest is growing in understanding whether the treatment effect varies among prespecified patient subpopulations, such as those defined by demographics or baseline clinical characteristics. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“… 37 Methodology for detecting treatment‐effect heterogeneity in cluster randomized trials is the topic of ongoing research. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 37 Methodology for detecting treatment‐effect heterogeneity in cluster randomized trials is the topic of ongoing research. 38 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…However, recent methodological results have revealed that detecting treatment‐effect heterogeneity in cluster randomized trials may not always require larger sample sizes than detecting the average treatment effect 37 . Methodology for detecting treatment‐effect heterogeneity in cluster randomized trials is the topic of ongoing research 38,39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watson et al investigated the impact of small sample sizes on the performance of a three‐arm parallel CRD 21 . Li et al 22 constructed a three‐level CRD with two covariates to assess treatment effect heterogeneity. Recent developments in CRDs and up to date references can be found in review papers 23,24 …”
Section: Introductionmentioning
confidence: 99%
“…Although the power analysis of the treatment-by-covariate interaction test has been relatively well-studied in individually randomized trials, 3,4,5 related methods for power analysis in CRTs have only received recent attention with the goal to enable a rigorous understanding of how system-level innovations may differentially impact outcomes for important subpopulations. 6,7,8,9,10 With a pre-specified effect modifier, Yang et al 8 developed an analytical sample size and power formula to test the treatmentby-covariate interaction, making it possible to power CRTs a priori for confirmatory HTE analyses. Similar to designing conventional CRTs to study the average treatment effect, the intracluster correlation coefficient (ICC) of the outcome, or outcome-ICC, plays an essential role in determining the power and necessary sample size for the HTE test.…”
mentioning
confidence: 99%